2018
DOI: 10.1001/jamadermatol.2017.3647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Administration of a Mixture of Probiotic Strains on SCORAD Index and Use of Topical Steroids in Young Patients With Moderate Atopic Dermatitis

Abstract: IMPORTANCE Oral intake of new probiotic formulations may improve the course of atopic dermatitis (AD) in a young population.OBJECTIVE To determine whether a mixture of oral probiotics is safe and effective in the treatment of AD symptoms and to evaluate its influence on the use of topical steroids in a young population. DESIGN, SETTING, AND PARTICIPANTSA 12-week randomized, double-blind, placebo-controlled intervention trial, from March to June 2016, at the outpatient hospital Centro Dermatológico Estético de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 42 publications
4
97
0
2
Order By: Relevance
“…These authors noted a significant improvement in SCORAD scores and quality of life indices following administration of the probiotics separately and in combination compared to placebo. In a setting with concomitant corticosteroid therapy similar to the present study, Navarro et al [18] presented strong evidence supportive of a reduction of the objective SCORAD and sparing of corticosteroid use following 12-week treatment of children aged 4–17 years suffering from moderate AD with a probiotic mixture of strains of Bifidobacterium lactis CECT 8145, Bifidobacterium longum CECT 7347, and Lactobacillus casei CECT9104. It is possible that the different results in similar study designs are primarily attributable to the choice of probiotic strains.…”
Section: Discussion/conclusionsupporting
confidence: 77%
“…These authors noted a significant improvement in SCORAD scores and quality of life indices following administration of the probiotics separately and in combination compared to placebo. In a setting with concomitant corticosteroid therapy similar to the present study, Navarro et al [18] presented strong evidence supportive of a reduction of the objective SCORAD and sparing of corticosteroid use following 12-week treatment of children aged 4–17 years suffering from moderate AD with a probiotic mixture of strains of Bifidobacterium lactis CECT 8145, Bifidobacterium longum CECT 7347, and Lactobacillus casei CECT9104. It is possible that the different results in similar study designs are primarily attributable to the choice of probiotic strains.…”
Section: Discussion/conclusionsupporting
confidence: 77%
“…Although atopic dermatitis usually occurs between 3 and 6 months of age, the onset of symptoms may also start at or before 2 months, the period approximately when NEC occurs (16). Some studies have reported the use of oral supplementations with probiotics in the treatment of atopic dermatitis, and their findings seem to indirectly strengthen the association between gut dysbiosis and the development of atopic dermatitis (17,18). Our results showed no significant increase in the risk of developing atopic dermatitis, allergic rhinitis, and asthma in the NEC patients (median followup times of 29, 37, 43 months, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Results from older meta‐analyses support the use of oral probiotics for the treatment of AD and even for prevention, suggesting that Lactobacillus alone and Lactobacillus with Bifidobacterium bifidum are protective against development of AD, with odds ratios of 0·7 and 0·62, respectively . Additionally, daily oral supplementation with a mixture of Bifidobacterium and Lactobacillus casei strains for 12 weeks in patients with moderate AD led to a 19·2‐point greater mean reduction in SCORAD compared with control patients . However, some effects may be strain or species specific, as probiotics with Lactobacillus rhamnosus and Lactobacillus paracasei have yielded mixed results …”
Section: Methodsmentioning
confidence: 99%
“…30 Additionally, daily oral supplementation with a mixture of Bifidobacterium and Lactobacillus casei strains for 12 weeks in patients with moderate AD led to a 19Á2point greater mean reduction in SCORAD compared with control patients. 31 However, some effects may be strain or species specific, as probiotics with Lactobacillus rhamnosus and Lactobacillus paracasei have yielded mixed results. [32][33][34][35][36] Thus far, few studies have utilized live bacteria in topical probiotics for treatment of AD.…”
Section: Atopic Dermatitismentioning
confidence: 99%